Peran Kepuasan Kerja Dalam Memediasi Pengaruh Lingkungan Kerja Dan Pengembangan Karir Terhadap Kinerja Pegawai - Tamara Farisa Putri; Muis Fauzi Rambe (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
The purpose of this study was to determine and analyze job satisfaction in mediating the influence of the work environment and career development on employee performance at the Regional Office of the Ministry of Law and Human Rights of North Sumatera. The sample in this study used a saturated sample, where all the population was sampled, but non-permanent or temporary employees were not included in the sample. The sample in this study amounted to 70 employees in the Administrative Division. The data collection technique in this study used a questionnaire, while the data analysis technique in this study used quantitative data analysis methods, with SEM-PLS statistical analysis. Data processing in this study using the software program SmartPLS 3.3.3. The results of this study prove that the work environment directly has a significant effect on job satisfaction, career development directly has a significant effect on job satisfaction, directly the work environment has no significant effect on performance, career development directly has a significant effect on performance, directly job satisfaction has no significant effect on performance, indirectly job satisfaction acts as a mediator between the work environment on performance, indirectly job satisfaction acts as a mediator between career development and performance at the Regional Office of the Ministry of Law and Human Rights of North Sumatera